Implementasi Struktur Tiga Babak dalam Penulisan Naskah Video Feature “Kopi Semangka” - Mutiara Amisyah; Encang Saepudin; Nurmaya Prahatmaja (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
The growth of the specialty coffee industry in Indonesia has driven various post-harvest processing innovations, one of which is coffee with a flavor character resembling watermelon (watermelon notes) produced by Fugol Cafe & Roastery through an anaerobic natural process without artificial flavoring. This phenomenon has not been widely discussed in audiovisual form, prompting the author to create a feature video titled "Kopi Semangka" by applying the three-act structure as a narrative framework in scriptwriting. This work aims to explain the implementation of the three-act structure in the First Act (Set-Up), Second Act (Confrontation), and Third Act (Resolution) in composing the script, referring to the concepts of Syd Field and Robert McKee. The creation process was carried out through pre-production, production, and post-production stages, with production taking place in Bandung and Jatinangor involving six interviewees consisting of a roaster, consumers, and an agricultural technology expert. The First Act builds the premise and hook through a rhetorical question regarding the origin of the watermelon flavor in coffee; the Second Act elaborates the scientific anaerobic natural process that shapes the flavor character gradually, supported by expert validation; while the Third Act presents a resolution in the form of consumer responses as social validation of the innovation introduced. The implementation of the three-act structure proved effective in systematically arranging the storyline, sustaining audience engagement, and conveying scientific information about agricultural product innovation in a narrative and easily understandable manner.